Perception of air pollution in Lima: contrast between Abancay Avenue and El Olivar San Isidro - Aramayo B., Armando (2012)
Air pollution is a growing problem in many cities, including Lima is a city that has more than 9 million people today. The lack of adequate mass transit system, the age of the existing public transport, high traffic congestion, the type of fuel used and the particular geography of the city has led to air pollution is a major problem in terms the management of the city. In the present study we are comparing two locations within the city of Lima: El Olivar, an area surrounded by many large trees and low level of vehicular traffic, and Abancay Avenue, an area known for being one of the ways most air pollution in the city, and through surveys has been raised to determine the existence of differences in the perceptions of people about some health problems related to air pollution that they could be earning. The results indicate that there are significant differences between what people perceive in these two places, the difference between men and women and is also very significant. Among the health problems whose difference is more noticeable highlights the irritation and itching of the eyes. In asthma there is no statistically significant difference between the two sites evaluated. Such studies related to environmental pollution can serve as a tool for environmental planning because it can help to identify fast and cheaply problem areas and to estimate levels of air pollution indirectly, based on the problems perceived by people .